Determination of Vitamin C Concentration in Various Fresh Orange and Lemon Samples from Janzour Region Using Volumetric Titration - Fatma Hebail, (AlQalam Journal of Medical and Applied Sciences, 2024)
Vitamin C is an essential nutrient crucial for human health, playing a vital role in numerous physiological processes, including immune system support and collagen synthesis. Citrus fruits, such as oranges and lemons, are recognized as rich sources of this vitamin. The primary purpose of this study is to determine the vitamin C concentration in various fresh orange and lemon juices. The samples were randomly collected from the local market in Janzour. The study included 18 samples representing 6 different citrus varieties (3 samples per variety). Vitamin C concentration was statistically estimated using a titrimetric method with a standardized solution of 2,6-dichlorophenolindophenol (DCPIP) as the titrant. The obtained results revealed some kind of variations in vitamin C content among different citrus varieties and even within samples of the same variety. Abu Surah orange samples exhibited the highest vitamin C concentration (mean range: 38.9-41.6 mg/dl), while sweet orange samples had the lowest (mean range: 5.1- 8.5 mg/dl). Vitamin C concentrations in other varieties ranged as follows: Sour orange: 9.22-24.9 mg/dl, Mandarin: 9.0 -16.2 mg/dl, Tarocco: 28.2-33.3 mg/dl, and Lemon: 14.5-15.8 mg/dl. These results showed evidently that vitamin C levels were varied even within the same sample type. Such variations would draw attention to the importance of choosing varieties when searching for food sources of this vital nutrient. يُعتبر فيتامين C عنصرًا غذائيًا أساسيًا بالغ الأهمية لصحة الإنسان، حيث يلعب دورًا حيويًا في العديد من العمليات الفسيولوجية، بما في ذلك دعم جهاز المناعة وتخليق الكولاجين. تشتهر الحمضيات، مثل البرتقال والليمون، بكونها مصادر غنية بهذا. لذا، هدفت هذه الدراسة إلى تقدير تركيز فيتامين C في عينات مختلفة من عصائر البرتقال والليمون الطازجة والتي تم جمعها عشوائيًا من السوق المحلي بمنطقة جنزور. شملت الدراسة 18 عينة من 6 أنواع مختلفة من الحمضيات (3 عينات من كل نوع). تم تقدير تركيز فيتامين C باستخدام طريقة المعايرة الحجمية بمحلول قياسي من صبغة 2,6- ثنائي كلورو فينول إندوفينول. أظهرت النتائج التي تم الحصول عليها من خلال هذه الدراسة تباينًا في تركيز فيتامين C بين أنواع الحمضيات المختلفة، بل وحتى بين عينات من نفس النوع. سجلت عينات برتقال أبو سرة أعلى تركيز لفيتامين C بمعدل (38.9-41.6 ملجم/ دل)، بينما سجلت عينات البرتقال الحلو أقل تركيز بمعدل (5.1-8.5 ملجم/ دل). تراوحت تراكيز فيتامين C في الأنواع الأخرى كالآتي: البرتقال الحامض بمعدل (9.22-24.9 ملجم/ دل)، اليوسفي بمعدل ( 9-16.2 ملجم/ دل)، التاروكي بمعدل (28.2-33.3 ملجم/ دل)،و الليمون بمعدل (14.5-15.8 ملجم/ دل) و من خلال هذه النتائج تم تسليط الضوء على التباين في مستويات فيتامين C حتى داخل نفس نوع العينة، مما يؤكد أهمية اختيار الأصناف عند البحث عن مصادر غذائية لهذه المغذيات الحيوية